2016
DOI: 10.1002/jmri.25348
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced and diffusion-weighted MRI of estrogen receptor-positive invasive breast cancers: Associations between quantitative MR parameters and Ki-67 proliferation status

Abstract: 4 J. Magn. Reson. Imaging 2017;45:94-102.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 37 publications
2
38
1
Order By: Relevance
“…4 Furthermore, ROC analysis suggests that K trans had higher sensitivity than k ep in diagnosing breast cancers at equal accuracy, consistent with that in other studies. 19,22,23 By contrast, Li et al 24 observed that k ep might better depict tumor capillary permeability than K trans because K trans may tend to be influenced by conditions influencing blood perfusion. However, k ep is not confounded by these factors.…”
Section: Discussionmentioning
confidence: 98%
“…4 Furthermore, ROC analysis suggests that K trans had higher sensitivity than k ep in diagnosing breast cancers at equal accuracy, consistent with that in other studies. 19,22,23 By contrast, Li et al 24 observed that k ep might better depict tumor capillary permeability than K trans because K trans may tend to be influenced by conditions influencing blood perfusion. However, k ep is not confounded by these factors.…”
Section: Discussionmentioning
confidence: 98%
“…The prognostic value of breast tumor MRI characteristics is an emerging area of research. Several studies have recently reported ADC measures to be associated with tumor grade and proliferation . However, these prior DWI studies have not focused specifically on hormone receptor‐positive, HER2‐negative invasive breast cancers, the most common but heterogeneous group of breast cancers, for which chemotherapy recommendation is variable in practice.…”
Section: Discussionmentioning
confidence: 99%
“…17 While DCE-MRI provides information about tumor vascularity, DWI reflects water mobility in tissue, characterizing tumor cellularity. Recent studies have shown DWI measurements to correlate with prognostic markers such as Nottingham grade, 18,19 Ki-67 score, [20][21][22][23] and expression of HER2, 22,24 and hormonal receptors 21,24 in invasive breast cancer. However, few studies specifically evaluate ER-positive cancers, 25 and to our knowledge only one published study to date has specifically investigated DWI as a potential predictor of RS.…”
mentioning
confidence: 99%
“…Within invasive disease, a number of studies have shown ADC values to negatively correlate with tumor grade [1721]. A similar correlation was seen with tumor proliferation, using Ki-67 index as a marker [13, 2126]. The ability to detect more aggressive tumors may aid in consideration of neoadjuvant treatment prior to surgery.…”
Section: Clinical Applicationsmentioning
confidence: 92%